(untitled) (Vietnam Journal of Community Medicine, 2024)
Audio ototoxicity refers to the damage with the inner structures of the ear (cochlea and vestibule) and their functions (hearing and balance) that can be experienced with exposure to certain drugs (eg, aminoside antibiotics, cisplatin, macrolides, etc.). Aminoside-associated ototoxicity is common to the doctor but hasn’t been recognized and noticed with macrolide. We report a case of a patient presenting with tinnitus and hearing loss when using macrolide antibiotics for a long time in the treatment of NTM.